Prevalence of Human Immunodeficiency Virus (HIV) Antibody Detection in Men Who Have Sex with Men (MSM): Prevalensi Deteksi Antibodi Human Immunodeficiency Virus (HIV) Pada Kelompok Lelaki Seks Lelaki (LSL) - Haq, Fhasya Algina Hawatul; Amelia, Ria; Sari, Elfira Maya; Luhulima, Danny Ernest Jonas (Medicra (Journal of Medical Laboratory Science/Technology), 2024)
Human Immunodeficiency Virus (HIV) infection is one of the infectious infections caused by HIV that attacks the lymphocytes T tipe CD4 and can cause a decrease in the immune system. Male Sex Men (MSM) have a higher risk of HIV infection due to MSM behavior, such as having direct anal sex without using condoms or lubricant products and are more likely to change sex partners frequently. This study aims to find out the results of rapid testing of HIV antibodies on MSM in Rawalumbu and Jaka Mulya urban village. This research uses cross sectional research design, its type of research is descriptive with selection and data collection purposively sampling that carried out in February – June 2024 in Rawalumbu and Jaka Mulya urban village. Thirty-five respondents were collected. The result from a rapid test of early HIV antibodies with rapid Reagen 1 (R1) in 35 respondents, 6 respondents (17%) were reactive and 29 respondents (83%) were non-reactive. HIV antibody reactive results is 6 respondents (17%) of total 35 respondents, the most reactive outcomes in the age category 26 – 36 years.